DESKRIPSI PEMAHAMAN KONSEP SISWA PADA MATERI BANGUN RUANG SISI DATAR DITINJAU DARI KEPRIBADIAN SENSING DAN INTUITION SISWA SMP - Sri Satriani; Didin Ferdiansyah; Ahmad Syamsuadi (Universitas Pekalongan, 2022)
Not all students can absorb the material well, therefore researchers are interested in conducting research related to how students obtain information based on their personality. This research is a qualitative research with descriptive method, aims to describe students' conceptual understanding with sensing and intuition personality, with 2 subjects. Data collection techniques are tests and interviews. The test used is a personality test to select the subject. Furthermore, a concept understanding test was given to see his ability based on seven indicators of concept understanding, after that an interview was conducted to get more information about understanding the concept. The measurement of concept understanding uses the results of diagnostic tests, namely able, less able, and unable. Understanding the concept of personality sensing (S1), which is less capable of indicators of restating concepts, developing necessary and sufficient conditions, and using, utilizing, and choosing certain procedures but being able to give examples and non-examples of indicators, presenting concepts in the form of mathematical representations, and apply concepts to problem solving. The emerging trend is to practically answer questions, focus on results, be specific and detailed in explanations. Careful in processing information and making decisions, as well as careful, realistic and concrete. The majority of indicators are understood by S1 so S1 tends to understand the concept. Understanding the concept of students with intuition personality (S2), which is less capable on indicators of developing necessary and sufficient conditions and using, utilizing, and choosing certain procedures but able on indicators of restating concepts, classifying objects based on their properties, giving examples and non examples, presenting concepts in the form of mathematical representations, and applying concepts to problem solving. The tendencies that emerge are imaginative, abstract, conceptual and answer in their own way. See the linkages and focus on the process. The majority of indicators are understood by masters, so masters tend to understand concepts.